Assessment of psychiatrists’ preparedness in managing disaster-related psychiatric disorders: a survey in Taiwan from post-graduate medical education perspective - Lin, Po-Chun; Chou, Yu-Ching; Kao, Lien-Cheng; Wan, Fang-Jung; Tzeng, Nian-Sheng (Frontiers in Psychiatry, 2024)
Background Disaster-related psychiatric disorders (DRPD) present a significant challenge to mental health professionals, yet there is a notable lack of emphasis on the preparedness of psychiatrists in managing these conditions within post-graduate medical education. Methods This study utilized a questionnaire to collect data from psychiatrists, focusing on their prior involvement in managing DRPD, perceived competence, medication preferences, and factors influencing their experiences in handling such disorders. Analysis included distribution and ranking of variables, alongside cross-analysis examining associations between demographic factors (age, gender, hospital levels, years of practice, board certification) and treatment experiences, as well as readiness for in-hospital or outside-hospital mobilization in DRPD management. Results One hundred and three Taiwanese psychiatrists participated in the study, with the majority reporting involvement in managing DRPD (71.8%), particularly in post-traumatic stress disorder (PTSD) and depression. Antidepressants, specifically serotonin selective reuptake inhibitors, were commonly preferred for DRPD treatment, including PTSD and depression. Psychiatrists aged over 40, with more than 10 years of practice, and hold the board-certified status, showed greater experiences for outside- or inside- the hospital mobilization in DRPD management. Conclusion Findings suggest that within post-graduate medical education, Taiwanese psychiatrists demonstrate significant experience, willingness, and capacity to effectively manage DRPD. However, there is a need to integrate comprehensive training on disaster psychiatry into post-graduate psychiatric education programs to further enhance preparedness and optimize outcomes in managing these challenging conditions.